The politics of gentrification: the case of west town in Chicago - Betancur, John J. (2002)
The author examines the local dialectics of power associated with gentrification in the community of West Town in Chicago, discussing the process, contentions resulting from opposite interests, strategies of the major players involved, and the painful and emotional struggles that have resulted from the advance of gentrification. Today, West Town is bitterly split between contending agents of gentrification and resistance. Although the process has not been completed, expectations have placed the community in a difficult position as institutions, businesses, and households feel its impact and wonder about the future. In particular, the role of class, race, and ethnicity in the process of gentrification is examined. - Reproduced.
Keywords: Urban renewal - United States; Urban renewal